Evaluation of salivary glucose, amylase, and total protein in Type 2 diabetes mellitus patients - M Indira; P Chandrashekar; Kiran Kumar Kattappagari; Lalith Prakash K Chandra; Ravi Teja Chitturi; Ramana Reddy BV (Wolters Kluwer Medknow Publications, 2015)
Background: Diabetes mellitus is a complex multisystem metabolic disorder characterized by a deficit in the production of insulin. The oral complications of uncontrolled diabetes mellitus are devastating. Saliva is an organic fluid that can be collected noninvasively and by individuals with limited training. These reasons create an interest in evaluating the possibility of using saliva as a diagnostic tool. Aims and Objectives: The aim of this study was to determine, if saliva can be used as a noninvasive tool to monitor glycemic control in Type 2 diabetes. Comparative assessment of salivary (glucose, amylase, total protein levels) in patients with Type 2 diabetes and controls. Materials and Methods: A total of 40 individuals, 20 with Type 2 diabetes and 20 controls of age group 40-60 years were selected for the study. Diabetic status was assessed by estimating random blood glucose levels. Unstimulated saliva was collected from each participant and investigated for glucose, amylase, and total protein levels. Salivary glucose estimation was performed using glucose-oxidase method, amylase by the direct substrate kinetic enzymatic method, and total protein by pyrogallol red dye end point method. All the parameters were subjected to statistical analysis using SPSS version 20.0. Results: Significantly higher salivary glucose, lower amylase, and total proteins were observed in patients with Type 2 diabetes than controls. There was no significant correlation between salivary and blood glucose levels. Conclusion: These results suggest that diabetes influences the composition of saliva. Since a significant correlation was not observed between salivary and blood glucose levels, further research is needed to determine salivary glucose estimation as a diagnostic tool for diabetes mellitus.